2019
DOI: 10.1002/cam4.2513
|View full text |Cite
|
Sign up to set email alerts
|

Sam68 is required for the growth and survival of nonmelanoma skin cancer

Abstract: Although targeting DNA repair signaling pathways has emerged as a promising therapeutic for skin cancer, the relevance of DNA damage responses (DDR) in the development and survival of nonmelanoma skin cancer (NMSC), the most common type of skin cancer, remains obscure. Here, we report that Src‐associated substrate during mitosis of 68 kDa (Sam68), an early signaling molecule in DDR, is elevated in skin tumor tissues derived from NMSC patients and skin lesions from Gli2‐transgenic mice. Downregulation of Sam68 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…SAM68 is known to play important roles in the regulation of mRNA processing, signal transduction, gene transcription, and DNA repair [ 33 , 54 ], and emerging evidence links SAM68 to pathogenic mechanisms, including cell proliferation, apoptosis, invasion, and metastasis in various human cancers [ 55 , 56 , 57 , 58 ]. Previous studies and our data here agree in that upregulation of SAM68 expression is associated with lung cancer progression and poor patient outcome [ 37 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…SAM68 is known to play important roles in the regulation of mRNA processing, signal transduction, gene transcription, and DNA repair [ 33 , 54 ], and emerging evidence links SAM68 to pathogenic mechanisms, including cell proliferation, apoptosis, invasion, and metastasis in various human cancers [ 55 , 56 , 57 , 58 ]. Previous studies and our data here agree in that upregulation of SAM68 expression is associated with lung cancer progression and poor patient outcome [ 37 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Sam68/PARP1 interaction is crucial for DNA damage-initiated, PARP1-dependent PARylation [ 42 ]. T61 resides in the N-terminal region of Sam68 ( Figure 3 A), which is required for the interaction with PARP1 and the downstream activation of NFκB upon DDR induction [ 42 , 53 ]. Thus, we asked if ATM-dependent phosphorylation of T61 could selectively regulate the Sam68–PARP1–NFκB axis.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanism involved in this protective function was not elucidated. Subsequent studies in other cellular systems revealed a crucial role for Sam68 in promoting PARP1 recruitment to DNA lesions and NF-κB activation in response to genotoxic stress [ 42 , 43 , 44 , 53 ]. These studies indicated that the N-terminus of Sam68 (aa 1-101) is crucial for the interaction with PARP1 and that this interaction potentiated DDR induction.…”
Section: Discussionmentioning
confidence: 99%
“…SAM68 can also promote polarization movements and cell migration independent of its RNA-binding activity (195). The positive role of SAM68 in tumor transformation has been demonstrated in other types of human cancer (196)(197)(198). It has been demonstrated that SAM68-deficient cells exhibit intron 5 retention in mTOR mRNA, resulting in an early termination codon and a reduction in the mTOR protein levels (199).…”
Section: Sam68mentioning
confidence: 99%